A fractographic study on the effects of hygrothermal conditioning on carbon fiber/epoxy laminates submitted to axial compression. (September 2017) - Opelt, C.V.; Paiva, J.M.F.; Cândido, G.M.; Rezende, M.C.
Abstract: This paper is part of a series of fractographic studies on fiber-reinforced polymer composites submitted to compression, which attempts to fill the gap in the composite failure analysis. Here, the effect of the hygrothermal conditioning is assessed for composite laminates manufactured from a carbon fiber/epoxy resin prepregs, which used plain weave fiber arrangement. The laminate was trimmed into compression test specimens, according to the ASTM D3410 standard. After the test, the aspects of the failure were investigated using a scanning electron microscope, so the compression failure modes could be identified. The fractographic analysis indicates that the lower compressive strength of the conditioned specimens was caused by a decrease in the stiffness of the polymer matrix, due to the plasticizing effect of the moisture exposure. Highlights: Effect of the aging on the compression failure was studied for polymer composites. The compression failure modes were analyzed from a fractographic outlook. The specimens tested without conditioning suffered irregular fracture propagation. Compression failure of the conditioned specimens was by through-thickness shear. The difference was attributed to the plasticizing effect of the moisture exposure.